Ascetic culture : essays in honor of Philip Rousseau - Leyerle, Blake, 1960-; Young, Robin Darling; Rousseau, Philip (University of Notre Dame Press, 2013)
This collection honors Philip Rousseau's pathbreaking work on early Christian asceticism in a series of essays exploring how quickly the industrious and imaginative practitioners of asceticism, from the early fourth through the mid-fifth century, adapted the Greco-Roman social, literary, and religious culture in which they had been raised. Far from rejecting the life of the urban centers of the ancient world, they refined and elaborated that life in their libraries, households, and communities. The volume begins with a discussion of Egyptian monastic reading programs and the circulation of texts, especially the hugely influential Life of Antony. A second group of essays engages the topic of disciplinary culture in ascetic spaces such as the monastery, the household, and the city. A third group focuses on the topic of imaginary landscapes and ascetic self-fashioning. The book concludes by surveying the scholarly study of asceticism over the last one hundred and fifty years, arguing that previous generations of scholars have regarded asceticism either as a product of the inner dynamism of early Christianity or as a distortion of its earliest aims. Together, the contributors recognize, reflect upon, and extend the themes explored in Rousseau's work on early Christianity's ascetic periphery - a region whose inhabitants reflect in various ways the aspirations of their religion, from the daily to the otherworldly.